Breaking Intergenerational Cycles of Repetition A Global Dialogue on Historical Trauma and Memory - Gobodo-Madikizela, Pumla (Verlag Barbara Budrich, 2016)
The authors in this volume explore the interconnected issues of intergenerational trauma and traumatic memory in societies with a history of collective violence across the globe. Each chapter's discussion offers a critical reflection on historical trauma and its repercussions, and how memory can be used as a basis for dialogue and transformation. The perspectives include, among others: the healing journey of three generations of a family of Holocaust survivors and their dialogue with third generation German students over time; traumatic memories of the British concentration camps in South Africa; reparations and reconciliation in the context of the historical trauma of Aboriginal Australians; and the use of the arts as a strategy of dialogue and transformation.